(untitled) (Research, Society and Development, 2022)
Objective: To analyze the bibliometric indicators about the scientific production available in the SciELO database that addresses the health of the indigenous elderly. Methodology: This is a bibliometric study, carried out with six articles published between 2013 and 2022 in the SciELO database. Results: All studies were carried out by nurses, most of them masters and doctors. The study also revealed that the indigenous elderly have difficulties in accessing health services, and thus, these factors end up directly interfering with the health of this population. In addition, it was observed that culture, language and other factors also influence their health. Final considerations: The study made it possible to identify bibliometric indicators on the scientific production in the area, low scientific production on the subject, reflecting the need to expand research on the health of indigenous peoples in order to expand the collection on the subject in question and subsidize better form the discussion related to the subject.